Mechanisms impairing blood pressure responses to nitrite and nitrate - Oliveira-Paula, Gustavo H.; Pinheiro, Lucas C.; Tanus-Santos, Jose E. (Nitric oxide, 2019)
Hypertension is a multifactorial disease associated with impaired nitric oxide (NO) production and bioavailability. In this respect, restoring NO activity by using nitrite and nitrate has been considered a potential therapeutic strategy to treat hypertension. This possibility is justified by the understanding that both nitrite and nitrate may be recycled back to NO and also promote the generation of other bioactive species. This process involves a complex biological circuit known as the enterosalivary cycle of nitrate, where this anion is actively taken up by the salivary glands and converted to nitrite by nitrate-reducing bacteria in the oral cavity. Nitrite is then ingested and reduced to NO and other nitroso species under the acid conditions of the stomach, whereas reminiscent nitrite that escapes gastric reduction is absorbed systemically and can be converted into NO by nitrite-reductases in tissues. While there is no doubt that nitrite and nitrate exert antihypertensive effects, several agents can impair the blood pressure responses to these anions by disrupting the enterosalivary cycle of nitrate. These agents include dietary and smoking-derived thiocyanate, antiseptic mouthwash, proton pump inhibitors, ascorbate at high concentrations, and xanthine oxidoreductase inhibitors. In this article, we provide an overview of the physiological aspects of nitrite and nitrate bioactivation and the therapeutic potential of these anions in hypertension. We also discuss mechanisms by which agents counteracting the antihypertensive responses to nitrite and nitrate mediate their effects. These critical aspects should be taken into consideration when suggesting nitrate or nitrite-based therapies to patients. [Display omitted] •Hypertension is associated with deficiet nitric oxide (NO) activity.•Nitrite and nitrate can be recycled back to NO in the enterosalivary cycle of nitrate.•Using nitrite and nitrate is now a promising antihypertensive strategy.•Agents disrupting the enterosalivary cycle of nitrate may prevent this effect.•This review focused on major mechanisms interfering with this effect.